Breastfeeding within a half hour postpartum and its effect on exclusive breastfeeding. - Bellido, Percy (2015)
Objective: To study the diminishing frequency of exclusive breast feeding and the effect of precocious breast feeding (PBF) and skin- skin contact (SSC) in exclusive breast feeding (EBF). Procedures: Study group (n=30): Skin to skin contact and breast feeding in the first half hour of the child birth and EBF control within 5-15 days. Control group (n=30): The same procedure but without SSC and PBE Prospective longitudinal study. Results: In the study group EBF was present in 93,33% in the first 5 days and in 73,3% in the first 15 days; in the control group EBF was present in 76,67% and 30% (p<0,05), respectively. Risk groups in which EBF decreases: Less than 21 years old, high school urban-marginal procedence and primigravid. Conclusion: The PBF and SSC is determinant to guarantee EBF in a short period.